The influence of space in the learning of architecture. Bauhaus Dessau and ENSA Nantes - Genís-Vinyals, Mariona; Maroto-Sales, Joan; Taberna Torres, Judit (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
When educational spaces are designed linked to a specific pedagogical practice, it allows, as has been proven throughout history, that architecture can be an active agent in teaching and learning processes. A transdisciplinary approach, from architecture, pedagogy and neuroscience, identifies two dimensions that influence this active role of space. There is a dimension linked to the morphological characteristics of the building in all its scales (classroom, common areas, building skin and connection with the city) and another related to the content of this building (furniture, objects, technologies) and its influence on the experience of its inhabitants /actors.This article analyzes the relationship between these two dimensions and pedagogical practice in the field of architecture schools. The analysis focuses on the buildings of the Bauhaus in Dessau and the School of Architecture in Nantes. The first to be one of the first architecture schools in which space is designed to be an active learning agent and the second because space is projected to expand this learning beyond the university environment.
Keywords: Active learning spaces; Pedagogy; Practice community; Bauhaus; ENSA Nantes